Microplastic pollution in finless porpoises and their habitats along the Fujian coast of the East China Sea - Wang, Daling; Zhen, Yu; Wei, Lili; Dai, Yufei; Wang, Xianyan; Tong, Shenhan; Zhao, Liyuan (Frontiers in Marine Science, 2022)
Microplastics (MPs) pose serious threats to various marine organisms, including many threatened apex predators such as cetaceans. However, information on microplastic contamination in cetaceans from Asian waters is limited. We reported MPs from nationally protected finless porpoise intestinal samples and from their habitats along the Fujian coast of the East China Sea. MPs proved to be ubiquitous in both intestinal and habitat water samples. Most intestinal MPs were fibers (86.90%), transparent (51.19%), small sizes (<1.0 mm, 77.38%), and composed of polyamide (41.67%) or polyethylene terephthalate (45.24%). Seawater MPs were predominantly fibers (90.25%), transparent (82.45%), < 1.0 mm (83.76%) and composed of polypropylene (67.32%). Concentrations of MPs in coastal waters were greater than those in offshore waters. The concentration and composition of fibrous MPs indicate a likely textile industry origin. A recommendation is made to further assess the risks of MPs consumption in threatened species and develop scientific protection and management strategies.